New information on environmental drivers for local adaptation of African indigenous chicken - CGIAR Research Program on Livestock (2021)
Breeding for climate resilience is currently an important goal for sustainable livestock production. The pre-identification of key environmental drivers, followed by genomic investigation, provides a powerful new approach for elucidating adaptation in domestic animals.